2010
DOI: 10.1111/j.1420-9101.2010.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic admixture increases fitness during a biological invasion

Abstract: During biological invasions, multiple introductions can provide opportunities for admixture among genetically distinct lineages. Admixture is predicted to contribute to invasion success by directly increasing fitness through hybrid vigour or by enhancing evolutionary potential within populations. Here, we demonstrate genome‐wide admixture during an invasion that substantially boosted fitness in the cosmopolitan weed, Silene vulgaris. We identified three divergent demes in the native European range that expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
238
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(250 citation statements)
references
References 65 publications
12
238
0
Order By: Relevance
“…Positive effects of admixture have been observed in invasive populations that show heterozygosity-fitness correlations in the introduced range [46,54]. The fitness benefits of a heterozygous genome are likely to be especially strong for small, declining and inbred populations of endangered species that are unable to purge deleterious mutations [55].…”
Section: (C) the Pros And Cons Of Genetic Admixturementioning
confidence: 99%
“…Positive effects of admixture have been observed in invasive populations that show heterozygosity-fitness correlations in the introduced range [46,54]. The fitness benefits of a heterozygous genome are likely to be especially strong for small, declining and inbred populations of endangered species that are unable to purge deleterious mutations [55].…”
Section: (C) the Pros And Cons Of Genetic Admixturementioning
confidence: 99%
“…Several population genetic studies have revealed mixed ancestries of invasive populations reflecting genetic admixture of multiple divergent native source populations (e.g., Kolbe et al., 2004; Rosenthal, Ramakrishnan, & Cruzan, 2008; Chun, Fumanal, Laitung, & Bretagnolle, 2010; Stephen R. Keller, Gilbert, Fields, & Taylor, 2012). Moreover, some studies also provide evidence for phenotypic changes and effects on fitness associated with admixture (Kolbe, Larson, & Losos, 2007; Facon, Pointier, Jarne, Sarda, & David, 2008; S. R. Keller & Taylor, 2010). However, although these observational studies suggest a strong link of genetic admixture and invasion success, it remains difficult to disentangle the direct effects of genetic admixture (e.g., heterosis) from long‐term effects of increases in genetic variation (evolutionary potential), as well as other confounding effects such as propagule pressure that may be associated with multiple introductions.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, one such factor is admixture among conspecific populations, which can increase standing genetic variation and generate novel, adaptive combinations resulting in enhanced adaptability at the range edge [27,28,32,33,58]. Nevertheless, lack of genetic variation in peripheral populations and lack of new beneficial mutations can still restrict the extent to which genetic exchange among conspecific populations enhances their adaptability at the range edge [57,59].…”
Section: Hybridization's Role In Range Expansionmentioning
confidence: 99%